Detection of radiation treatment in frozen meat through analysis of its lipids' thermal behavior and liquid crystalline state - Millare, Jean M.; Dumelod, Benelyn Domingo (2003)
ABSTRACT The Bligh and Dyer method was employed to isolate lipids from irradiated and control frozen beef, pork and chicken meat samples. The lipid extracts were analyzed using different scanning calorimetry (DSC) and optical polarizing microscopy (OPM) to determine any difference between the treated and non-treated samples. A peak temperature of approximately 18.31°C is observed from the thermograms of control chicken lipids. For the treated samples, two peaks are seen, occurring at about 19.54 and 37.63°C. For the control and treated pork lipids, peak temperatures of around 22.30 and 36.88°C and 22.38 and 32.84°C, respectively, are observed. As for the lipids from beef, the peak temperatures for the control are observed at approximately 17.17 and 34.48°C while for the irradiated samples, these are seen at around 17.61 and 33.22°C. Non-irradiated chicken lipids exhibit characteristic liquid crystalline formations that are absent in the irradiated samples. For pork, both the irradiated and non-irradiated liquid samples show evidence of liquid crystal formations. For beef, no liquid crystals are seen in the radiation-treated lipid samples as well as in the control. The results show that it is possible to detect radiation treatment in frozen chicken meat through analysis of its lipid components using DSC and OPM. For frozen pork, DSC may be used as a detection method but further investigation is needed because the second peak of the treated sample is exhibited only by two of the three trials. However, OPM cannot be applied for frozen pork. For frozen beef, both DSC and OPM cannot be used to distinguish irradiated from non-irradiated sam
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Radiation preservation of food